Peran Kreativitas Bahasa Promosi pada Konten Digital E-Commerce - Elsa Celina Pasaribu; Nadhilah Arifah Ginting; Romaida Nasution; Yohana Graciola Sibarani; Nadra Amalia (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The rapid growth of e-commerce in the digital era encourages companies to develop innovative marketing communication strategies. One of the key factors that determine the success of digital marketing is the creativity in promotional language. Creative promotional language not only serves to attract consumer attention but also builds emotional closeness, increases engagement, and strengthens brand image amidst increasingly competitive markets. The use of persuasive, interactive, and audience-relevant language styles creates differentiation and influences purchasing decisions. Therefore, the creativity of promotional language plays a strategic role in enhancing the effectiveness of digital ecommerce content while supporting business sustainability in the digital era.